Synthesis, Characterization, and Antibacterial Activity of Some Mesalazine Derivatives - Ekhlas Qanber Jasim; Munther Abduljaleel Muhammad-Ali; Ayad Almakki (Science and Technology Indonesia, 2023)
Mesalazine, often referred to as mesalamine or 5-aminosalicylic acid (5-ASA), and its derivatives are some of the first medications to be approved for treating digestive tract inflammations, including ulcerative colitis and mild to moderate Crohn’s disease. Sulfasalazine, discovered in 1938 for therapeutic use, was the first mesalazine derivative. High yields of four different mesalazine derivatives were synthesized, including two Schiff bases and two azo compounds. The present study involved the synthesis of Schiff bases through the reaction of mesalazine with pyrrole-2-carbaldehyde or indole-2-carbaldehyde, resulting in the formation of 5-(((1H-pyrrol-2-yl)methylene)amino)-2-hydroxybenzoic acid (1) or 5-(((1H-indol-2-yl)methylene)amino)-2hydroxybenzoic acid (2), respectively. The synthesis of azo compounds involved the coupling of mesalazine with sulfamethoxazole or pyridoxine, resulting in the formation of 5-amino-2-hydroxy-3-((4-(N-(5-methylisoxazol-3-yl)sulfamoyl)phenyl)diazenyl)benzoic acid (3) or 2-hydroxy-5-((5-hydroxy-3,4-bis(hydroxymethyl)-6-methylpyridin-2-yl)diazenyl)benzoic acid (4), respectively. The identification of the synthesized compounds was carried out using IR and 1H-NMR spectroscopy. Antibacterial assessment of the synthetic compounds was performed in vitro against gram-negative bacteria (such as Escherichia coli and Pseudomonas aeruginosa) and gram-positive bacteria (Staphylococcus aureus). The antibacterial activity studies demonstrated that against Escherichia coli and Staphylococcus aureus, the Schiff base compounds are more active than azo compounds. Compound 1 showed the highest activity, resulting in a 23 mm inhibition zone against E. coli at 1000 ug/ml. In contrast, the antibacterial activity of compound 2 was observed to be 25 mm against S. aureus at the same highest concentration.